2020
DOI: 10.1111/nuf.12495
|View full text |Cite
|
Sign up to set email alerts
|

An examination of nurse‐authored patents: Implications for nursing practice

Abstract: Background Recognition for medical inventions and innovations is largely associated with physician‐researchers, scientists, and engineers. The term “nurse” is largely absent from patents awarded in the United States. Yet, as front‐line healthcare providers, who better to add to the current population of inventors and innovators of new, meaningful scientific and engineering medical discoveries than specialized advanced practice nurses and their registered nurse colleagues? Although medical inventions and innova… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Although nurses and nursing students are not traditionally taught innovation, business and entrepreneurial skills, many often ideate solutions to daily work challenges. Despite representing one of the largest workforce segments in health care, nurses are credited with the least number of patents, documented discoveries, and the ability to view themselves as innovators ( Davis & Glasgow, 2020 ). We deduced that nurses and nursing students did not view themselves as innovators and lacked a higher level of confidence conducive to the challenges and difficulties involved in business venture startup.…”
Section: Discussionmentioning
confidence: 99%
“…Although nurses and nursing students are not traditionally taught innovation, business and entrepreneurial skills, many often ideate solutions to daily work challenges. Despite representing one of the largest workforce segments in health care, nurses are credited with the least number of patents, documented discoveries, and the ability to view themselves as innovators ( Davis & Glasgow, 2020 ). We deduced that nurses and nursing students did not view themselves as innovators and lacked a higher level of confidence conducive to the challenges and difficulties involved in business venture startup.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, a recent study found that the term "nurse" was largely absent from patents awarded in the United States (Davis & Glasgow, 2020). The innovative capabilities of nurses can help to improve patient care experiences, practices and outcomes, reduce health care costs and outcomes (Davis & Glasgow, 2020), and produce personal benefits and organizational operational performance (Moreira M R A et al, 2017). Therefore, there is an urgent need to develop and train the innovative capabilities of nurses.…”
Section: Discussionmentioning
confidence: 99%
“…However, previous studies have found that nurses had varying levels of innovative behaviours (Bunpin et al, 2016; Liu, 2019; Sönmez & Yıldırım, 2019), moderate level of innovation ability (Jiang et al, 2020), and average level of innovation outputs (Sönmez et al, 2019). Meanwhile, a recent study found that the term “nurse” was largely absent from patents awarded in the United States (Davis & Glasgow, 2020). The innovative capabilities of nurses can help to improve patient care experiences, practices and outcomes, reduce health care costs and outcomes (Davis & Glasgow, 2020), and produce personal benefits and organizational operational performance (Moreira M R A et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Nurses have likely had a moment in their career when they think to themselves, “Nobody asked a nurse how to design this!” Nurses functioning in any professional role can have an impact on patient care, workflow, and efficiency through care innovation, product development, and new inventions. Nurses are responsible for innovative devices such as the Bili-Bonnet , used to hold eye protection in place for infants undergoing treatment for jaundice, and Colorsafe , an intravenous line color-coding system 1 . Unfortunately, few nurses have opportunities to create and contribute to patient care in this way.…”
mentioning
confidence: 99%
“…Unfortunately, few nurses have opportunities to create and contribute to patient care in this way. An absence of nursing presence on patents and in groups that are developing new technologies and products is a missed opportunity for improving patient care experiences and patient outcomes, and perhaps reducing health care costs 1 . Introducing nursing students to the idea that nurses can and do function as inventors is essential to inspiring these future nurses to innovate.…”
mentioning
confidence: 99%